Allergic rhinitis: Review of the diagnosis and management: South African Allergic Rhinitis Working Group - Guy A. Richards; Marinda McDonald; Claudia L. Gray; Pieter de Waal; Ray Friedman; Maurice Hockman; Sarah J. Karabus; Cornelia M. Lodder; Tshegofatso Mabelane; Sylvia M. Mosito; Ashen Nanan; Jonny G. Peter; et al. (South African Family Practice)
Background: Allergic rhinitis (AR) has a significant impact on the community as a whole with regard to quality of life and its relationship to allergic multi-morbidities. Appropriate diagnosis, treatment and review of the efficacy of interventions can ameliorate these effects. Yet, the importance of AR is often overlooked, and appropriate therapy is neglected. The availability of effective medications and knowledge as to management are often lacking in both public and private health systems.